Perancangan Dashboard Monitoring Berbasis Android pada Sistem Medis Troli Otonom SIMETRI - Rafli Gymnastiar; Dian Budhi Santoso; Indri Purwita Sary; Jordan Zefanya Purba; Galih Setyaji (Program Studi Teknik Elektronika Politeknik Negeri Malang, 2026)
The development of digital technology has encouraged the use of Android-based monitoring applications to support more efficient healthcare systems. The Integrated Autonomous Medical Trolley System (SIMETRI) requires a monitoring dashboard that enables users to monitor system conditions easily and flexibly. This study aims to design an Android-based monitoring dashboard for SIMETRI using HTML, CSS, and JavaScript developed in Visual Studio Code and converted into an Android application using AppsGeyser. The research method includes system design, dashboard development, and testing using Black Box Testing and White Box Testing. The results show that the application was successfully developed with Login, Dashboard, Monitoring, and Controlling features that function properly on Android devices. The testing results indicate that all application functions operate according to the design, demonstrating that the dashboard can be used as a monitoring platform for SIMETRI.